Real-life results of urate-driven pharmacotherapy with three urate lowering drugs in gout: allopurinol, febuxostat and benzbromarone - Ioana Hotea; Tanja Giesen; Antoaneta Comarniceanu; Monique Efde; Frits van Osch; Matthijs Janssen; Tim L. Jansen (Exploration of Musculoskeletal Diseases)
Aim: This study aims to assess outcomes of gout patients from the treat to target (T2T) perspective at 6 months and 12 months while using urate lowering therapy (ULT): allopurinol, febuxostat, and/or benzbromarone. Methods: All gout patients visiting the Rheumatology department between 2015 to 2021 were identified from the digital hospital system. The diagnosis of gout was based on the American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) 2015 classification criteria. Patient outcomes were predefined intention to treat (ITT) categories: category 1: patients with serum uric acid (sUA) ≤ 0.360 mmol/L (ACR target for gout); category 2: patients with sUA ≤ 0.300 mmol/L (ACR/EULAR target for severe gout); category 3: patients with sUA > 0.360 (failure to meet ACR target). Results: Gout diagnoses were present in 1,186 patients: 986 (83.1%) males and 200 (16.9%) females. A follow-visit at 6 months was present in 76.9% (n = 856) out of 1,113 patients reaching sUA < 0.36 mmol/L, but 257 (23%) failed to reach the 0.36 mmol/L target. At 12 months, a follow-up visit was available in 792 (71.1%) patients, and from these, 710 (90%) had reached sUA < 0.36 mmol/L target. The use of benzbromarone was a strong predictor of reaching the sUA < 0.30 mmol/L target: odds ratio (OR) 3.2, 95% confidence interval (CI) (1.735, 6.017) at 6 months. Diabetic patients had the highest proportion of not reaching the target: 18%. Male patients needed higher dosages of allopurinol to reach the sUA target at 6 months compared to female patients. Conclusions: This is a large study on a T2T approach based in a real-life clinical setting. Only 42% reached the sUA target at 6 months with allopurinol 300 mg quaque die (QD) monotherapy. About 77% of gout patients reach the predefined sUA target of 0.36 mmol/L at 6 months with the availability of three ULTs. There is still a significant unmet need in gout as many patients failed to achieve predefined sUA targets.